THE HUBUNGAN ANTARA KEBUGARAN FISIK DENGAN DISMENORE PRIMER PADA REMAJA PUTRI DI SMA NEGERI 1 DENPASAR TAHUN 2014 - Dewa Agung Gina Andrini; Dedi Silakarma; Adiartha Griadhi (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Dysmenorrhea is one of the common problems experienced by most of the adolescent girls. Some factors that can prevent primary dysmenorrhea to occur is to do sports or physical fitness. The statement problem of this research is whether there is a correlations between physical fitness with primary dysmenorrhea among adolescent girls in SMA Negeri 1 Denpasar. Author applied analytic study design with cross sectional approach as the research method. Technique that was being used to determine the sample is simple random sampling. Number of samples was 49 adolescent girls at SMA Negeri 1 Denpasar. The data analysis technique was by chi square test. Based on the results of the 15 respondents who were fit, there were 6 people (40%) had experienced primary dysmenorrhea and 9 people (60%) had not experienced primary dysmenorrhea. While of 34 respondents who were not fit, there were 30 people (88,2%) had experienced primary dysmenorrhea and 4 (11,8%) had not experienced primary dysmenorrhea. From data analysis by using chi square test, the value of p obtained is 0.000 (p < 0,05). Based on the statistic tests it can be concluded that there is a significant correlation between physical fitness with primary dysmenorrhea.